Effectiveness of Alternative Victim Assistance Service Delivery Models in the San Diego Region, 1993-1994 - Rienick, Cynthia ([Verlag nicht ermittelbar], 2000)
This study had a variety of aims: (1) to assess the needs of violent crime victims, (2) to document the services that were available to violent crime victims in the San Diego region, (3) to assess the level of service utilization by different segments of the population, (4) to determine how individuals cope with victimization and how coping ability varies as a function of victim and crime characteristics, (5) to document the set of factors related to satisfaction with the criminal justice system, (6) to recommend improvements in the delivery of services to victims, and (7) to identify issues for future research. Data were collected using five different survey instruments. The first survey was sent to over 3,000 violent crime victims over the age of 16 and to approximately 60 homicide witnesses and survivors in the San Diego region (Part 1, Initial Victims' Survey Data). Of the 718 victims who returned the initial survey, 330 victims were recontacted six months later (Part 2, Follow-Up Victims' Survey Data). Respondents in Part 1 were asked what type of violent crime occurred, whether they sustained injury, whether they received medical treatment, what the nature of their relationship to the suspect was, and if the suspect had been arrested. Respondents for both Parts 1 and 2 were asked which service providers, if any, contacted them at the time of the incident or afterwards. Respondents were also asked what type of services they needed and received at the time of the incident or afterwards. Respondents in Part 2 rated the overall service and helpfulness of the information received at the time of the incident and after, and their level of satisfaction regarding contact with the police, prosecutor, and judge handling their case. Respondents in Part 2 were also asked what sort of financial loss resulted from the incident, and whether federal, state, local, or private agencies provided financial assistance to them. Finally, respondents in Part 1 and Part 2 were asked about the physical and psychological effects of their victimization. Demographic variables for Part 1 and Part 2 include the marital status, employment status, and type of job of each violent crime victim/witness/survivor. Part 1 also includes the race, sex, and highest level of education of each respondent. Police and court case files were reviewed six months after the incident occurred for each initial sample case. Data regarding victim and incident characteristics were collected from original arrest reports, jail booking screens, and court dockets (Part 3, Tracking Data). The variables for Part 3 include the total number of victims, survivors, and witnesses of violent crimes, place of attack, evidence collected, and which service providers were at the scene of the crime. Part 3 also includes a detailed list of the services provided to the victim/witness/survivor at the scene of the crime and after. These services included counseling, explanation of medical and police procedures, self-defense and crime prevention classes, food, clothing, psychological/psychiatric services, and help with court processes. Additional Part 3 variables cover circumstances of the incident, initial custody status of suspects, involvement of victims and witnesses at hearings, and case outcome, including disposition and sentencing. The race, sex, and age of each victim/witness/survivor are also recorded in Part 3 along with the same demographics for each suspect. Data for Part 4, Intervention Programs Survey Data, were gathered using a third survey, which was distributed to members of the three following intervention programs: (1) the San Diego Crisis Intervention Team, (2) the EYE Counseling and Crisis Services, Crisis and Advocacy Team, and (3) the District Attorney's Victim-Witness Assistance Program. A modified version of the survey with a subset of the original questions was administered one year later to members of the San Diego Crisis Intervention Team (Part 5, Crisis Intervention Team Survey Data) and to the EYE Counseling and Crisis Services, Crisis and Advocacy Team (Part 6, EYE Crisis and Advocacy Team Survey Data). The survey questions for Parts 4-6 asked each respondent to provide their reasons for becoming involved with the program, the goals of the program, responsibilities of the staff or volunteers, the types of referral services their agency provided, the number of hours of training required, and the topics covered in the training. Respondents for Parts 4-6 were further asked about the specific types of services they provided to victims/witnesses/survivors. Part 4 also contains a series of variables regarding coordination efforts, problems, and resolutions encountered when dealing with other intervention agencies and law enforcement agencies. Demographic variables for Parts 4-6 include the ethnicity, age, gender, and highest level of education of each respondent, and whether the respondent was a staff member of the agency or volunteer. The fourth survey was mailed to 53 referral agencies used by police and crisis interventionists (Part 7, Service Provider Survey Data). Part 7 contains the same series of variables as Part 4 on dealing with other intervention and law enforcement agencies. Respondents in Part 7 were further asked to describe the type of victims/witnesses/survivors to whom they provided service (e.g., domestic violence victims, homicide witnesses, or suicide survivors) and to rate their level of satisfaction with referral procedures provided by law enforcement officers, hospitals, paramedics, religious groups, the San Diego Crisis Intervention Team, the EYE Crisis Team, and the District Attorney's Victim/Witness Program. Part 7 also includes the hours of operation for each service provider organization, as well as which California counties they serviced. Finally, respondents in Part 7 were given a list of services and asked if they provided any of those services to victims/witnesses/survivors. Services unique to this list included job placement assistance, public awareness campaigns, accompaniment to court, support groups, and advocacy with outside agencies (e.g., employers or creditors). Demographic variables for Part 7 include the ethnicity, age, and gender of each respondent. The last survey was distributed to over 1,000 law enforcement officers from the Escondido, San Diego, and Vista sheriff's agencies (Part 8, Law Enforcement Survey Data). Respondents in Part 8 were surveyed to determine their familiarity with intervention programs, how they learned about the program, the extent to which they used or referred others to intervention services, appropriate circumstances for calling or not calling in interventionists, their opinions regarding various intervention programs, their interactions with interventionists at crime scenes, and suggestions for improving delivery of services to victims. Demographic variables for Part 8 include the rank and agency of each law enforcement respondent.